The Suicide Squad [videorecording (Blu-Ray + DVD)] - Gunn, James, 1966-; Robbie, Margot, 1990-; Elba, Idris; Cena, John; Kinnaman, Joel, 1979-; Davis, Viola, 1965-; Dastmalchian, David; Melchior, Daniela, 1996-; Courtney, Jai; Capaldi, Peter; Rooker, Michael, 1955-; Braham, Henry, 1965-; et al. (Warner Bros. Entertainment, 2021)
Task force X has been in constant service, but also must constantly recruit new members as the Suicide Squad lives up to its name. For a mission on the island of Corto Maltese, only Waller knows what Colonel Flag and his cons from Belle Reve will face, but team is in for a surprise -- and an enemy -- of epic proportions.